2022
DOI: 10.1111/codi.16167
|View full text |Cite
|
Sign up to set email alerts
|

Programmed cell death ligand 1 expression on monocytes is inversely correlated with tumour response to preoperative chemoradiotherapy for locally advanced rectal cancer

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…It was found that the higher the ratio of infiltrating CD8 + T cells to effector Tregs cells in tumor tissue, the better the efficacy. In addition, PD-L1 positivity, Ki-67 expression of tumor infiltrating CD8 + T cells, and CMS1 and CMS3 typing of CRC also predicted high response to chemoradiotherapy ( 75 ). In a prospective phase 2 study, all 12 patients (100%) with dMMR stage II or III rectal adenocarcinoma had a clinical complete response when treated with dostarlimab, with no evidence of tumor on imaging examination ( 76 ).…”
Section: Application Of Biomarkers In the Treatment Of Digestive Syst...mentioning
confidence: 99%
“…It was found that the higher the ratio of infiltrating CD8 + T cells to effector Tregs cells in tumor tissue, the better the efficacy. In addition, PD-L1 positivity, Ki-67 expression of tumor infiltrating CD8 + T cells, and CMS1 and CMS3 typing of CRC also predicted high response to chemoradiotherapy ( 75 ). In a prospective phase 2 study, all 12 patients (100%) with dMMR stage II or III rectal adenocarcinoma had a clinical complete response when treated with dostarlimab, with no evidence of tumor on imaging examination ( 76 ).…”
Section: Application Of Biomarkers In the Treatment Of Digestive Syst...mentioning
confidence: 99%
“…The quality of circulating T-cells and monocytes has also been investigated in a limited number of studies on rectal cancer. Tojo et al assessed the presence of PD-L1 expressing monocytes in the blood of rectal cancer patients [150]. A high percentage of this subpopulation before and after CRT correlated with low T-cell counts and was significantly linked with poor response to therapy.…”
Section: Systemic Immune Responsementioning
confidence: 99%